2009
DOI: 10.1111/j.1365-2141.2009.07633.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of genes encoding for proteins involved in heparan sulphate and chondroitin sulphate chain synthesis and modification in normal and malignant plasma cells

Abstract: Summary Syndecan‐1 is a proteoglycan that concentrates heparin‐binding factors on the surface of multiple myeloma cells, and probably plays a major role in multiple myeloma biology. As heparan sulphate and chondroitin sulphate are the bioactive components of syndecan‐1, we analysed the signature of genes encoding 100 proteins involved in synthesis of these chains, i.e. from precursor uptake to post‐translational modifications, using Affymetrix microarrays. The expression of enzymes required for heparan sulphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 64 publications
2
47
3
Order By: Relevance
“…In addition to HS, CD138 also bears another sulfated glycan structure in the form of chondroitin sulfate chains. 30,31 Inhibition by heparitinase but not chondroitinase confirmed that APRIL binding was dependent on HS, and showed that chondroitin sulfate structures were not involved. The complete inhibition seen with sodium chlorate and heparitinase further shows that HS on CD138 mediated the primary binding of soluble APRIL on MM cells without involvement of the signaling receptors TACI and BCMA.…”
Section: In Vivomentioning
confidence: 71%
“…In addition to HS, CD138 also bears another sulfated glycan structure in the form of chondroitin sulfate chains. 30,31 Inhibition by heparitinase but not chondroitinase confirmed that APRIL binding was dependent on HS, and showed that chondroitin sulfate structures were not involved. The complete inhibition seen with sodium chlorate and heparitinase further shows that HS on CD138 mediated the primary binding of soluble APRIL on MM cells without involvement of the signaling receptors TACI and BCMA.…”
Section: In Vivomentioning
confidence: 71%
“…Heparin is the exclusive product of mast cells (36). In contrast, B cells express the enzymes to produce highly sulfated heparan sulfate (37), and splenocytes indeed synthesize the most highly sulfated heparan of any tissue except the heart (38). The preference of VH56R/Vk38c IgM for heparin over poorly sulfated heparan sulfate strongly suggested that VH56R/Vk38c IgM can bind highly sulfated heparan sulfate in the Golgi of B cells.…”
Section: Gycosaminoglycan Binding Of Vh56r/vk38c Igmmentioning
confidence: 99%
“…Plasma cell differentiation is also associated with the expression of a high density of syndecan-1, with the necessity to continuously synthesize large levels of heparan sulfate chains and to import glucose. 29 In mammalian Table 3 Primary myeloma cells are stimulated by insulin or IGF-1, and the anti-INSR mAb or the anti-IGF-1 inhibits their survival were cultured for 5 days at 5 Â 10 5 cells/ml in serum-medium free without cytokine or with either insulin (100 ng/ml) or IGF-1 (100 ng/ml). To study the role of human serum insulin or IGF-1, primary myeloma cells were cultured in RPMI-1640 medium and 5% AB serum with either the anti-INSR mAb (1 mg/ml) or IGFBP-3 (2 mg/ml).…”
Section: Discussionmentioning
confidence: 99%